Lung cancer and socio‐economic status: inextricably linked to place of residence. Issue 5 (May 2017) - Denton, Eve J.; Hart, David; Russell, Prue A.; Wright, Gavin; Conron, Matthew
Abstract : Background: The association between socio‐economic status (SES) and lung cancer is internationally established, but in Australia this relationship remains ill defined. Aims: To examine the association between SES, place of residence and lung cancer outcomes in a large Australian cohort. Methods: A total of 2369 consecutive lung cancer patients managed by St Vincent's Hospital lung multidisciplinary meeting between 2001 and 2014 were included. Postcode data stratified participants by Socio‐economic indexes for areas, a validated measure of SES, and by geographical location, an important socio‐economic factor in Australia. Results: There was no difference between socio‐economic groups in age (68 years), sex (63% males) or presentation (75% symptomatic). Low socio‐economic patients had increased smoking rates and a trend towards less adenocarcinoma. More low SES patients were from rural locations, had a greater frequency of earlier stage disease and curative treatment with higher overall survival even after multivariate analysis. When stratified for SES, overall 5‐year survival was significantly better in the low SES group (33 vs 24%, n = 2275, P = 0.02), although stage‐stratified survival was similar in all socio‐economic groups. Conclusions: Low SES patients were more frequently from rural locations and unexpectedly had earlier stage disease and higher overall survival. The excellent outcomes in rural and lower SES patients are reassuring, but suggest that there is a population of these patients with advanced lung cancer who are not referred for multidisciplinary care. Further studies are required to define this group better and determine the barriers to referral to improve overall lung cancer outcomes.